Geriatric Odontoid Fractures: Treatment Algorithms of the German Society for Orthopaedics and Trauma Based on Expert Consensus and a Systematic Review. Issue 1 (April 2023) - Osterhoff, Georg; Scholz, Matti; Disch, Alexander C.; Katscher, Sebastian; Spiegl, Ulrich J. A.; Schnake, Klaus John; Scheyerer, Max J.
Study Design: Systematic review/expert consensus. Objectives: Fractures of the axis represent the most frequent injury of the spine in elderly patients. Both, operative and non-operative treatment are associated with a high rate of complications and mortality. The aim of this article was to summarize the current literature on the management of odontoid fractures in geriatric patients and to weigh it based on an expert consensus process. Methods: In a joint consensus process, members of the Spine Section of the German Orthopaedic and Trauma Society (DGOU) aimed to formulate recommendations for the diagnostic workup and treatment of odontoid fractures in geriatric patients. Based on the previously published recommendations, this article is an updated version with incorporating a systematic review of the recent literature. Results: Based on the new data available, the recommendations established in the initial consensus process were adapted. Conclusions: Computed tomography represents the diagnostic standard for patients with suspected injuries of the upper cervical spine. Anderson/D'Alonzo odontoid fractures type 1, non-displaced type 2, and type 3 can be treated conservatively. Even non-unions do not necessarily result in poor clinical outcome. In Anderson/D'Alonzo type 2 fractures, surgical therapy offers the advantage of relatively safe osseous healing with no increased complication rate even in elderly patients and can thus be recommended. In very high aged patients, however, a case-by-case decision should be made. When surgical stabilization of osteoporotic odontoid fractures is indicated, posterior techniques are biomechanically advantageous and can be considered the standard.